Pythium and Fungus Can Coexist in Keratitis - Hitendra Ahooja; Sharddha Yadav; Neelam Sapra; Neeru Chhikara (Delhi Journal of Ophthalmology)
This case report comprises a 22-year-old male presenting with right eye pain, redness, and watering. Initial treatment included antibiotics, antifungals, and oral steroids, but with poor response. Subsequent diagnosis revealed a central corneal descemetocele with Aspergillus flavus and Pythium dual infection. Therapeutic penetrating keratoplasty was performed followed by topical linezolid and later topical steroid therapy, resulting in successful management. This case highlights the importance of considering mixed infections like Pythium in refractory fungal ulcers, emphasizing the need for prompt diagnosis and required therapeutic interventions to achieve favorable outcomes.